Rancang Bangun Website Company Profile dengan CMS WordPress untuk Inari Sushi Indonesia - Bara, Iwan Bara; Achmar, Yuda Fatahillah; Amalia, Amalia (DBESTI: Journal of Digital Business and Technology Innovation, 2025)
The presence of a digital platform, such as a website, is crucial for enhancing business visibility and competitiveness. Inari Sushi Indonesia lacks an official digital medium, prompting this research to design and develop an informative, professional, and user-friendly website-based company profile. Development used WordPress with the Waterfall method, involving a preliminary study, design, implementation, and testing via User Acceptance Testing (UAT) across 8 scenarios with 3 respondents (owner, visitor, and IT staff). The results indicate that the website operates effectively, is responsive, and demonstrates 98% device compatibility with optimal loading times. Open interviews confirmed user satisfaction with navigation and information clarity. The conclusion affirms the system's suitability and effectiveness in supporting Inari Sushi’s digital presence and recommends future development of interactive features.